Revolutionizing Medicine with Liposomal Innovations: Pioneering Therapeutics and Diagnostics for the Future - Mamatha H S,; Ashok Kumar BS,; Disha NS, (The Bioscan, 2025)
Modern medicine is revolutionized through the introduction of liposomes - versatile nanocarriers comprising a phospholipid bilayer. Liposomes can encapsulate both hydrophilic and lipophilic material, while having customizable surface modification, thus it finds significant applications in targeted drug delivery, controlled release, and enhanced therapeutic efficacy. Doxil® and AmBisome® have already improved cancer and infectious diseases by making treatments significantly reduce systemic toxicity while increasing bioavailability. Functionalized liposomes with ligands, imaging agents, or stimuli-responsive components have advanced gene therapy, CNS drug delivery, and precision medicine. In diagnostics, liposomes enable imaging and biosensing by encapsulating contrast agents such as gadolinium, which allows for the visualization of disease-specific conditions with higher sensitivity. Theranostic liposomes combine therapy and diagnostics, allowing for real-time monitoring of treatment. Applications include ophthalmology, dermatology, vaccine delivery, and CNS therapy, overcoming the blood-brain barrier. Liposomes improved drug penetration in skin treatments and elicited strong immune responses in vaccines. As the research continues, it tends to evolve with multifunctional platforms in solving unmet medical needs with transformative potential in oncology, infectious diseases, diagnostics, and personalized medicine.